Effect of Fluorescent Particle Size on the Modulation Efficiency of Ultrasound-Modulated Fluorescence - Yuan Liu; Baohong Yuan; Joseph Vignola (International Journal of Optics)
To investigate whether the size of fluorescent particles affects the modulation efficiency of ultrasound-modulated fluorescence (UMF), we measured UMF and DC (direct current) signals of the fluorescence emission from four different-sized fluorescent particles: (1) three carboxylate-modified fluorescent microspheres (FM) with diameters of 20 nm, 200 nm, and 1.0 μm and (2) streptavidin-conjugated Alexa Fluor 647 with a diameter of approximately 5 nm. The UMF and DC signals were simultaneously measured using a broadband lock-in amplifier and a narrowband amplifier, respectively. The ratio of the UMF strength to the DC signal strength is defined as the modulation efficiency. This modulation efficiency was then used to evaluate the effects of fluorophore size and concentration. Results show that the modulation efficiency was improved by approximately a factor of two when the size of the fluorescent particles is increased from 5 nm to 1 μm. In addition, the linear relationship between the UMF strength and ultrasound pressure (observed in our previous study) was maintained regardless of the fluorescent particle sizes.